Which Combination of Game Elements Can Lead to a Useful Gamification in Education? Evidence from a Fuzzy-set Qualitative Comparative Analysis - Mouna Denden; Ahmed Tlili; Ahmed Hosny Saleh Metwally; Huanhuan Wang; Ahmed Mohamed Fahmy Yousef; Ronghuai Huang; Haijun Zeng; Rustam Shadiev (Open Praxis)
Despite the importance of gamification in education, there is still ongoing debate in the literature about how to design effective and useful educational gamification. This is because gamification is a complex concept that requires combining various game elements together. To further contribute to this discussion, this study first develops a gamified course, using seven game elements, where eighty-three university students were enrolled in the course during an entire semester (three months). It then builds on the complexity theory and fuzzy-set Qualitative Comparative Analysis (fsQCA) to investigate which combination of the seven game elements can explain students’ perceived usefulness of gamification in the given course. The findings revealed that no single game element leads to students perceiving gamification useful. Additionally, the evidence from this study suggests that there are ten solutions which can explain the students’ perceived usefulness of gamification in the course. Particularly, badge was the most present game element in these solutions, where it is found in eight among the ten solutions. The findings of this study can guide various stakeholders (e.g., educators, designers and developers) on how to create a useful educational gamification, hence enhancing learning experiences and outcomes.